Simulation of multilayer metamaterials - Man, Mengren. (2010)
A new class of non-magnetic optical metamaterials capable of achieving negative refraction for all incident angles is thoroughly analyzed in this thesis. This new design consists solely of periodically stratified planar media, as first proposed by Hoffman et al., which obviates the fabrication difficulty and high intrinsic losses associated with conventional metamaterial designs involving resonant structures, and is less susceptible to fabrication inaccuracies. In this non-magnetic multilayer design, negative refraction is achieved via anisotropy in permittivity tensor, rather than simultaneously negative electric permittivity and magnetic permeability. The overall composite forms a macroscopically homogeneous uniaxial medium, and is capable of achieving negative refraction of Poynting vector for TM-polarized light incident from isotropic medium. In this thesis, multilayer metamaterials are analyzed from two perspectives, both as homogeneous effective medium and as stratified media. The analyses are in terms of transmission and reflection spectra calculated with transfer matrix method, as well as full-wave simulation with Finite-Element Method (FEM) using COMSOL Multiphysics. It is demonstrated that negative refraction can be achieved with many material combinations including InGaAs/AlInAs and Ag/Al2O3 which are arranged in a pattern of alternating layers of intrinsic and heavily doped semiconductors or metal and dielectric. By using metals or extrinsic semiconductors with different plasma frequencies and loss characteristics, the regime of negative refraction can be shifted over a wide range of spectrum, from mid-infrared with semiconductors to visible spectrum with metals, which spans the entire spectrum of interest to applications in optical imaging and communications. The new multilayer metamaterial design proves to be customizable, of low loss at optical frequencies and easy to fabricate. It is hoped that this work will influence future metamaterials designs and their incorporation into semiconductor photonic devices.